A Direct‐Push Freezing Core Barrel for Sampling Unconsolidated Subsurface Sediments and Adjacent Pore Fluids - Trost, J.J. (2020)
This technology has not previously been compatible with direct‐push rigs that are commonly used for contaminated site assessments. Here, we describe a freezing core barrel designed for direct‐push rigs that is compatible with commercially available tool strings. The device can be used interchangeably with unsaturated‐zone direct‐push tool strings, enabling core collection for studies of contaminant transport and transformation spanning unsaturated to saturated profiles. In all 10 attempts during testing near Bemidji, MN, the device froze a 10‐ to 15‐cm (4–6‐in) plug that retained fluids and sediments in a 1.2‐m (4‐ft)‐long, 5.0‐cm (2.0‐in)‐diameter polyvinyl chloride (PVC) sleeve. Cores were collected from variably saturated sediments spanning the capillary fringe through the upper 2 m of the saturated zone in sandy glacial outwash sediments. The median recovery was 81% of the drive length, similar to a sample‐freezing drive shoe developed for a wire‐line piston core sampler operated with a hollow‐stem auger drill rig.